Wood production and Its correlation with socioeconomic and environmental indicators in the Amazon region - Silva, Edwin Francisco Ferreira (2023)
In the Amazon region, land-use cover change has been identified as the primary factor responsible for deforestation and CO2 emissions. Concurrently, the average sawn yield of wood industries in the Amazon serves as a vital sustainability indicator due to its linkage with forest degradation and CO2 emissions. The first part of this study reviews published works and proposes a unified value of 46.54% with a standard deviation of 7.07% for the sawn yield in the State of Pará—Amazon Region. In the second part of this study, principal component analysis is applied to a ten-year historical series, from 2008 to 2018, encompassing 14 indicators across all 144 municipalities of the State of Pará. The results suggest that the socioeconomic dimension, with component loadings between 0.86 and 0.96, is predominantly influenced by population, value-added tax, and the number of households with electric consumption. The number of medical doctors per 1000 people (DOC) is also tied to the socioeconomic dimension, presenting component loadings between 0.72 and 0.80. Indicators such as cattle, deforestation, and CO2 emissions correlate with the environmental dimension, registering component loadings above 0.7. The factors examined embody the Amazon’s socioeconomic and environmental problems, including cattle rearing, deforestation, agricultural areas, and consequent CO2 emissions. Indeed, deforestation and CO2 emissions arise primarily from agriculture and animal husbandry, particularly cattle rearing. Wood production indicators yield low values of component loadings, suggesting a weak correlation with the environmental dimension. However, they simultaneously imply that wood production activity has been associated with CO2 emissions since 2014 and is therefore connected to land-use change. In summary, this work’s analysis suggests that wood products and wood residues are linked not only to socioeconomic factors but also to forest degradation and CO2 emissions.